2015
DOI: 10.1186/s12957-015-0454-4
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetable consumption and the risk of pancreatic cancer: a meta-analysis

Abstract: BackgroundPrevious studies regarding the association between cruciferous vegetable intake and pancreatic cancer risk have reported inconsistent results. We conducted a meta-analysis to demonstrate the potential association between them.MethodsA systematic literature search of papers was conducted in March 2014 using PubMed, EMBASE, and Web of Science, and the references of the retrieved articles were screened. The summary odds ratios (ORs) with 95% confidence interval (CI) for the highest versus the lowest int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…Our studies have demonstrated that purified sulforaphane is able to overcome the pronounced therapy resistance of PDA in vitro and in vivo [7,8], and similar results have been obtained in experimental models of prostate and breast cancer [8][9][10][11]. Epidemiological studies have suggested that the frequent intake of cruciferous vegetables might be inversely associated with the risk of developing pancreatic cancer [12][13][14][15][16], as well as cancer of the breast, kidney, bladder and prostate [17][18][19][20][21][22]. A Canadian study observed a significantly decreased risk of extra-prostatic manifestations of stage III and IV prostate cancer when men frequently consumed broccoli and cauliflower [17].…”
Section: Introductionsupporting
confidence: 82%
“…Our studies have demonstrated that purified sulforaphane is able to overcome the pronounced therapy resistance of PDA in vitro and in vivo [7,8], and similar results have been obtained in experimental models of prostate and breast cancer [8][9][10][11]. Epidemiological studies have suggested that the frequent intake of cruciferous vegetables might be inversely associated with the risk of developing pancreatic cancer [12][13][14][15][16], as well as cancer of the breast, kidney, bladder and prostate [17][18][19][20][21][22]. A Canadian study observed a significantly decreased risk of extra-prostatic manifestations of stage III and IV prostate cancer when men frequently consumed broccoli and cauliflower [17].…”
Section: Introductionsupporting
confidence: 82%
“…Following this line of research, pancreatic cancer is responsible for 4.5% of the total number of deaths in 2018 [112]. In 2015, Li [103] showed that cruciferous plant consumption might be inversely associated with pancreatic cancer risk. Nevertheless, given that the number of studies included in this research is scarce, further evidence needs to be included in future meta-analyses.…”
Section: Functionality: What Has Been Demonstrated and What Remains Tmentioning
confidence: 99%
“…Isothiocyanates are breakdown products of glucosinolates, and sulforaphane is produced from the precursor glucoraphanin, a major glucosinolate found in broccoli . A meta‐analysis of cohort and case control studies has suggested cruciferous vegetable intake may reduce the risk of breast and pancreatic cancer . Epidemiological data has been useful in highlighting the potential anti‐carcinogenic effect of cruciferous vegetables; however, identifying the most potent anti‐carcinogenic compounds within these foods is more difficult.…”
Section: Isothiocyanates – Sulforaphanementioning
confidence: 99%